Estimation of Peoples' Perception on Climate Change Effect on Agriculture: A Participatory and Socio-personal Analysis - A Jena and S K Acharya, (Indian Journal of Extension Education, 2016)
Climate change has been recognized globally as an ever increasing threat. The economic and social implications of globalclimate change are the subject of intense national and international study in present day scenario. The present study hasdelved deeper into the peoples' perception on congenital effect of climate change on agriculture in regards to coastal agroecosystem of Odisha. The study has been based on a blend between participatory rural appraisal and a conventionalmultivariate statistical analysis including correlation coefficient, multiple regression analysis, path analysis, factor andcanonical covariate analysis. Almost every year, within a cohort of last 53 years, coastal agriculture of Odisha hasexperienced brunt of 40 years of drought, flood or cyclones. This has been reflected in the stagnating yield of food cropsover the couple of decades, negating the positive impact of modern technology and fertilizer application in the operatingfarms. The result shows that, the variables like, age (X1), education (X2) & changing expenditure allocation on education(X10), change pattern of watching television, listening to radio, all have been redeemed into a dependable estimator ofperception on climate change effect on agriculture.